EFFECTIVENESS OF DIFFERENTIATION EFEKTIVITAS PEMBELAJARAN BERDIFERENSIASI TERHADAP KETERAMPILAN SOSIAL SISWA KELAS IV MATA PELAJARAN IPAS - Lestari, Siska; Arafat, Yasir; Murjainah, Murjainah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research aims to determine the effectiveness of differentiated learning on the social skills of class IV students in science subjects at SDN 19 Kelapa. The population in this study were 21 class IV students. The sample in this study amounted to 21 people. The sampling technique in this research was using a saturated sampling technique. The method used in this research is an experimental method in the form of Pre-Experimental Designs with the One-Group Pretest-Posttest Design type. Data collection was obtained using activity, observation and documentation rubrics. The data analysis techniques used in this research are normality testing and hypothesis testing. The results of the data analysis data calculations obtained an average posttest result value of 81 (good) in the category